1992
DOI: 10.1021/bi00155a002
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of prostaglandin endoperoxide synthase by N-acetylimidazole: Comparison to acetylation by aspirin

Abstract: Treatment of prostaglandin endoperoxide (PGH) synthase apoprotein with a 100- or 1000-fold excess of N-acetylimidazole (NAI) led to time-dependent inactivation of both cyclooxygenase and peroxide activities. Reconstitution of apoprotein with heme prior to incubation with NAI substantially protected the enzyme from inactivation. Pretreatment of the protein with either acetylsalicylic acid (aspirin) or (+/-)-2-fluoro-alpha-methyl-4-biphenylacetic acid (flurbiprofen), which inhibit cyclooxygenase activity, did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Thus, A-(carboxyheptyl)maleimide is between 5 and 3 orders of magnitude more potent than aspirin, depending on the time of preincubation. The exquisite sensitivity of cyclooxygenase inhibition to the structure of the substituted maleimides is consistent with our previous suggestion that the sensitivity of Ser530 to acetylation by aspirin is dependent on complementary interactions between the salicylate moiety and PGHS (Wells & Marnett, 1992). Furthermore, it raises the possibility that other covalent inactivators could be designed to differentially inhibit the two isoforms of PGHS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, A-(carboxyheptyl)maleimide is between 5 and 3 orders of magnitude more potent than aspirin, depending on the time of preincubation. The exquisite sensitivity of cyclooxygenase inhibition to the structure of the substituted maleimides is consistent with our previous suggestion that the sensitivity of Ser530 to acetylation by aspirin is dependent on complementary interactions between the salicylate moiety and PGHS (Wells & Marnett, 1992). Furthermore, it raises the possibility that other covalent inactivators could be designed to differentially inhibit the two isoforms of PGHS.…”
Section: Discussionsupporting
confidence: 89%
“…Covalent modification of PGHS is responsible for enzyme inactivation by acetylsalicylic acid (Robinson & Vane, 1974;Rome et al, 1976), acylimidazoles (Wells & Marnett, 1992Scherer et al, 1992), acyl-A-hydroxysuccinimides (Wells & Marnett, 1993), and A-alkylmaleimides (Kennedy et al, 1993). In all these cases, inactivation is time-dependent and occurs at ratios of inhibitor/enzyme of 100 or greater.…”
mentioning
confidence: 99%
“…These experiments further indicate that acetylation of iNOS [and/or essential cofactor(s)] inactivates its catalytic activity and that the potency of NAI is relatively greater than that of aspirin. NAI, which is commonly used for acetylation of tyrosine hydroxyl (28)(29)(30), acetylates protein residues at rates proportional to their nucleophilicity and accessibility (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that approximately, 33% of the covalent drugs in the market are anti-infectives (most notably the β-lactam class of antibiotics), 20% treat cancer, 15% treat gastrointestinal disorders, and ~15% are used to treat central nervous system and cardiovascular indications [ 14 ]. The earliest example of a covalent drug is aspirin, which was first marketed over a century ago; aspirin covalently modifies cyclooxygenase by inducing the acetylation of a serine residue that is situated in the active site ( Figure 1 A) [ 15 , 16 , 17 , 18 ]. β-lactam antibiotics are other examples of a covalent drug which acylate the active site serine of penicillin-binding proteins (PBPs) and kill the bacteria by inhibiting the final step of cell wall biosynthesis.…”
Section: Covalent Interactions In Biological Systemsmentioning
confidence: 99%